Terobosan dan Perubahan Kebijakan Ekonomi pada Masa Pemerintahan Umar bin Abdul Aziz dalam Mewujudkan Kesejahteraan Sosial - Nurani Puspa Ningrum; Yuliawati Yuliawati (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2020)
Abstract: This study aims to find out how the breakthroughs and policy change during the reign of Caliph Umar bin Abdul Aziz in the context of prospering his people, using qualitative methods that are used descriptively. The sources used are historical sources using library data. The result shows that public financial management policy of Caliph Umar bin Abdul Aziz is by optimizing state revenue by using zakat as the main source, optimizing jizyah, kharaj, usyur, ghanimah/fai, and taxes (dharibah). Improving the people’s welfare by optimizing the budget for people's welfare by created a good economic facilities and fixed up the agriculture fields. Whilst the impact of the policy carried out by Umar bin Abdul Aziz is an increase in people’s welfare, an increase in people's purchasing power, a reduction in poverty, a reduction in taxes because many of them changes theis faith to Islam, and those enhancement as the realization of the high islamic’s commitment in brotherhood and prosperity. Attainment of welfare was not only material or physical satisfaction, but also the fulfillment of spiritual needs as the capital for development. Keywords: Policy, State Revenue, State Expenditure, Caliph Umar bin Abdul Azi